Du menteur au fraudeur : ouï-dire et racontages: la voix de l'enfance retrouvée d'Eugène Savitzkaya - Almeida, José Domingues de (2018)
This paper will start from two novels by the Belgian Francophone writer of Slavic origin, Eugène Savitzkaya, published by Minuit, in which he looks back on his Walloon childhood and on his mothers figure by resorting to narrative strategies involving the hearsay, repetition and storytelling, as well as the flipping of albums and collage of many memories. Indeed, Mentir (1977), an eminently poetic and rhythmic novel, indicated this authors entry into fiction, nicknamed the muezzin because of his attachment to a poetic and rhythmic voice, the continued monotonous chant or to repetition as continued voice(s). However, in 2015, after an intense and more than once awarded literary production, Eugène Savitzkaya returns to this past and this technique in Fraudeur, in which the writer allies the consciousness of the irremediable passage through fiction.